EFEKTIFITAS PENGGUNAAN MINYAK ZAITUN PADA PEREMPUAN MENOPOUSE DENGAN XEROSIS KUTIS DENGAN METODE ADAPTASI ROY - Maria, Lisda; Astrid Suwendra Kusuma (LPPM STIKes Mitra Adiguna, 2025)
Menopause is a natural phase that marks the end of menstruation and reproduction in women. One of the complaints that is often experienced during menopause is xerosis cutis (dry skin), which has an impact on comfort and quality of life. This study aims to determine the effectiveness of using olive oil on skin moisture in menopausal women using Roy's adaptation theory approach. This study used a pre-experimental design with a one group pretest-posttest design. The sample consisted of 74 menopausal women who experienced xerosis cutis and were selected using a purposive sampling technique*. The study was conducted from January to February 2025 in the Sekip Palembang Health Center work area. Data analysis using the Wilcoxon test showed a p value = 0.000 (p <0.05), which indicated a significant effect of using olive oil on increasing skin moisture. These results indicate that olive oil can be used as an alternative skin care intervention in menopausal women. It is hoped that health workers, especially nurses, can integrate interventions based on Roy's adaptation theory in providing holistic nursing care.